2017
DOI: 10.18546/lre.15.2.05
|View full text |Cite
|
Sign up to set email alerts
|

The useful past in negotiation: Adolescents' use of history in negotiation of inter-group conflict

Abstract: Much of the concern with young people's historical knowledge centres on factual attainment or disciplinary skills. However, relatively little attention is paid to the relevance that young people attribute to history and how they use the past, and various social representations of history, to relate to the present. Research in this realm tends to emphasize the impact of collective memory narratives on individuals, rather than individuals' agency in using them. In this article, I will examine the ways 155 Jewis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Still, recent research has shown that history students (and others) tend to rely on what could be perceived as rather traditional renderings of the past, in particular when it comes to the national past (e.g., Angier, 2017;Goldberg, 2017;Vinterek et al, 2017). Canadian researcher Stéphane Lévesque argues that national histories and narratives are particularly salient to how we construct identities and make sense of ourselves and the world around us.…”
Section: Research Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…Still, recent research has shown that history students (and others) tend to rely on what could be perceived as rather traditional renderings of the past, in particular when it comes to the national past (e.g., Angier, 2017;Goldberg, 2017;Vinterek et al, 2017). Canadian researcher Stéphane Lévesque argues that national histories and narratives are particularly salient to how we construct identities and make sense of ourselves and the world around us.…”
Section: Research Contextmentioning
confidence: 99%
“…This view is accentuated by Israeli researcher Tsafrir Goldberg who studied how Palestinian and Israeli adolescents mobilised history in discussions among each other. Even though the informants were provided with textbook accounts and source material of their national past, they chose to rely on personal and more traditional historical accounts since they resonated with their personal beliefs and opinions of their national pasts (Goldberg, 2017). These results seem to suggest that national history goes well beyond being a topic that is suitable for an objective disinterested exercise in history, but rather relates strongly to deeply seated aspects of identity and citizenhood.…”
Section: Research Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…In situations with diverse-opposed historical claims, for example, in modern Israel where Jews and Arabs, each with their own version of 'their history' try to substantiate claims of exclusive ownership of the land-which is partly the result of diverse history curricula which have been offered to them in their respective schools (Goldberg, 2017)-a more open approach to history avoiding the 'we-group' and in search of a more distantiated common ground, could perhaps create new opportunities for dialogue. Creating historical distance as a conscious choice, unnatural and counter-intuitive as it is, could, therefore, be beneficial to the development of a stronger democratic and cosmopolitan identity.…”
Section: Historical Distancementioning
confidence: 99%